Consequences of germline variation disrupting the constitutional translational initiation codon start sites of MLH1 and BRCA2: Use of potential alternative start sites and implications for predicting variant pathogenicity. Issue 7 (2nd December 2013) - Parsons, Michael T.; Whiley, Phillip J.; Beesley, Jonathan; Drost, Mark; de Wind, Niels; Thompson, Bryony A.; Marquart, Louise; Hopper, John L.; Jenkins, Mark A.; Australasian Colorectal Cancer Family Registry; Brown, Melissa A.; Tucker, Kathy; et al.
<x xml:space="preserve">Abstract</x> Variants that disrupt the translation initiation sequences in cancer predisposition genes are generally assumed to be deleterious. However, few studies have validated these assumptions with functional and clinical data. Two cancer syndrome gene variants likely to affect native translation initiation were identified by clinical genetic testing: MLH1:c.1A>G p.(Met1?) and BRCA2:c.67+3A>G. In vitro GFP‐reporter assays were conducted to assess the consequences of translation initiation disruption on alternative downstream initiation codon usage. Analysis of MLH1:c.1A>G p.(Met1?) showed that translation was mostly initiated at an in‐frame position 103 nucleotides downstream, but also at two ATG sequences downstream. The protein product encoded by the in‐frame transcript initiating from position c.103 showed loss of in vitro mismatch repair activity comparable to known pathogenic mutations. BRCA2:c.67+3A>G was shown by mRNA analysis to result in an aberrantly spliced transcript deleting exon 2 and the consensus ATG site. In the absence of exon 2, translation initiated mostly at an out‐of‐frame ATG 323 nucleotides downstream, and to a lesser extent at an in‐frame ATG 370 nucleotides downstream. Initiation from any of the downstream alternative sites tested in both genes would lead to loss of protein function, but further clinical data is required to confirm if these variants are associated with a high cancer risk. Importantly, our results highlight the need for caution in interpreting the functional and clinical consequences of variation that leads to disruption of the initiation codon, since translation may not necessarily occur from the first downstream alternative start site, or from a single alternative start site. © 2013 Wiley Periodicals, Inc.